Meta analisis peran model pembelajaran contextual teaching dalam meningkatkan hasil belajar matematika dan sains siswa - Nabil Makarim; Wardhani Rahayu; Meiliasari Meiliasari; Anny Sovia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This research aims to evaluate the effectiveness of the Contextual Teaching and Learning (CTL) model on student learning outcomes. Conventional learning, which tends to focus on material memorization,. Therefore, CTL is viewed as a potential solution. The meta-analysis method was employed to synthesize findings from 19 quasi-experimental articles published (2011-2026), utilizing quantitative data. The analysis results indicate that the CTL model significantly enhances student learning outcomes, as evidenced by consistently higher mean scores in the experimental group. The heterogeneity test suggested variability across studies (Q = 69.30, p < .001), yet a significant pooled effect (t = 7.90, p < .001) affirmed the general effectiveness of CTL. Moderator variable analyses (educational level, subject matter, and geographical region) did not reveal significant influences, indicating that these factors do not substantially explain the variability in findings. These findings reinforce the claims of CTL's effectiveness as a student-centered and relevant learning strategy, although further research is necessary to deeply explore the factors that moderate its impact.